2015
DOI: 10.1155/2015/708272
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function, Prevalent Coronary Heart Disease, and Severity of Coronary Atherosclerosis in Patients Undergoing Coronary Angiography

Abstract: This study investigated if free T4 and TSH concentrations or thyroid function categories were associated with prevalent CHD and the severity of coronary atherosclerosis in a population undergoing coronary angiography. This was a cross-sectional study including 1799 patients who were consecutively admitted and underwent coronary angiography. We evaluated the severity of coronary atherosclerosis using Gensini score. In the entire study population, free T4 level was inversely associated with prevalent CHD (OR = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…The elevated level of 1-arachidonoyl-GPC (20:4n6), shown previously to be linked with increased CHD risk [ 15 ], was associated with increased cholesterol, alkaline phosphatase and T4, but lower homocysteine, LDL-cholesterol, total cholesterol and chloride. Elevated serum alkaline phosphatase and T4 were shown previously to be associated with the risk of CHD [ 39 , 40 ], possibly contributing to the increased CHD risk associated with the higher BMI group. Linolenate (18:3n3 or 6) was associated with elevated c-peptide, DBP, T3 and total iron-binding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated level of 1-arachidonoyl-GPC (20:4n6), shown previously to be linked with increased CHD risk [ 15 ], was associated with increased cholesterol, alkaline phosphatase and T4, but lower homocysteine, LDL-cholesterol, total cholesterol and chloride. Elevated serum alkaline phosphatase and T4 were shown previously to be associated with the risk of CHD [ 39 , 40 ], possibly contributing to the increased CHD risk associated with the higher BMI group. Linolenate (18:3n3 or 6) was associated with elevated c-peptide, DBP, T3 and total iron-binding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Hintze et al observed a rate of 3.8% of subclinical hyperthyroidism in 788 patients with IHD before undergoing coronary angiography, while another study from Germany observed 0.3% . More recently, Marraccini et al reported that hyperthyroidism was 2% of 1572 patients admitted for coronary angiography, and Ling et al studied 1799 consecutive adults over 30 who underwent coronary angiography for suspected IHD who showed less than 1% of spontaneous hyperthyroidism at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other studies that drew the opposite conclusion that neither FT4 nor TSH was related to ln (Gensini score). 26 It is worth noting that Lee et al 9 found that SCH was associated with re-PCI after in-stent restenosis, suggesting that SCH may aggravate coronary lesions by increasing stent intimal hyperplasia. We also observed that the severity of coronary artery lesions in patients with SCH was significantly higher than that in patients with ET.…”
Section: Subgroup Analysismentioning
confidence: 98%